Oral History and Reflective Subject: epistemological, conceptual and practical aspects (Research, Society and Development, 2020)
The objective of this article is to recover the pertinence of the use of the Oral History method in Organizational Studies that privilege the human point of view on work. There is a concern in addition to the epistemic aspects, in dealing with methodological aspects related to the operationalization of research in a pertinent way. Although the method has been known and used in Brazil for almost fifty years, there is still room for discussion on several aspects related to its relevance and use. We tried to discuss the conception of the method first, dealing with historical and conceptual aspects. Then, aspects related to the operationalization of the research, mainly of the necessary care for the researcher to be in the field. As a conclusion, it is understood that in a research involving the work context and the valorization of workers' knowledge, the use of the method allows a certain empowerment and transformation of subjects, as it allows participants to reflect and social awareness.